Assessment of diets containing curcumin, epigallocatechin-3-gallate, docosahexaenoic acid and alpha-lipoic acid on amyloid load and inflammation in a male transgenic mouse model of Alzheimer's disease: Are combinations more effective? - Sharman, Matthew J (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2020)
10.1016/j.nbd.2018.11.026